การบริหารงานของหัวหน้าหอผู้ป่วยที่ได้รับรางวัลดีเด่น Nursing Management of Head Nurses Receiving the Outstanding Award - รัตติกาลสุขะ จิราภรณ์; อ่วมตานี อารีย์วรรณ (Journal of The Royal Thai Army Nurses, 2014)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อบรรยายประสบการณ์การบริหารงานของหัวหน้าหอผู้ป่วยที่ได้รับรางวัลดีเด่น โดยใช้ ระเบียบวิธีวิจัยแบบปรากฏการณ์วิทยาการตีความ ผู้ให้ข้อมูลคือหัวหน้าหอผู้ป่วยที่ได้รับรางวัลดีเด่นจากฝ่ายการพยาบาล โรงพยาบาลระดับตติยภูมิแห่งหนึ่ง จำนวน 14 คน รวบรวมข้อมูลโดยใช้การสัมภาษณ์แบบเจาะลึกและนำข้อมูลที่ได้มาถอดความ แบบคำต่อคำ และวิเคราะห์เนื้อหาตามวิธีการของ Diekelman ผลการวิจัยมีดังนี้ 1. พัฒนาตนให้มีความรู้ บริหารตนสู่ความสมดุล ประกอบด้วย 3 ประเด็นย่อย 1.1) เรียนรู้จากรุ่นพี่ ประสบการณ์ที่มีเก็บสิ่งดี ๆ มาพัฒนา 1.2) ไม่หยุดการค้นคว้า หาเวลา ศึกษาอย่างต่อเนื่อง และ 1.3) แบ่งให้เวลากับงาน พอกลับบ้านแยกงานจากชีวิตส่วนตัว 2. ลูกน้องต้องสนับสนุน สร้างต้นทุนการทำงาน ประกอบด้วย 5 ประเด็นย่อย 2.1) สนับสนุนให้สร้างงาน เพิ่มความเชี่ยวชาญสู่การเป็นวิทยากร 2.2) ส่งเสริมความสามารถ สร้างคน สร้างโอกาสให้เรียนต่อ 2.3) รับฟังปัญหา คอยเป็นที่ปรึกษาและแก้ปัญหาเวลาติดขัด 2.4) สร้างบรรยากาศการทำงานเหมือนเป็นบ้านที่สองของทุกคน และ 2.5) มอบหมายงานตามความสามารถ เปิดโอกาสตัดสินใจได้เต็มที่ 3. โครงการต้องสร้างสรรค์ บริหารงานอย่างจริงใจ ไม่เห็นแก่ใคร แต่ใช้ตามหลักการ ประกอบด้วย 4 ประเด็นย่อย 3.1) พัฒนาโครงการ ตอบสนองงานตามนโยบาย นำมาประยุกต์ใช้ในหน่วยงาน 3.2) บริหารด้วยความจริงใจ ใช้หลักความยุติธรรมมีธรรมะในการทำงาน 3.3) มีความสามารถ บริหารคนได้ บริหารงานดี มีภาวะผู้นำ และ 3.4) ทุ่มให้งานอย่างเต็มที่ มีท้อใจบ้าง แต่ไม่ปล่อยวาง ยังมุ่งมั่นทำงานต่อไป จากผลการศึกษานี้ ทำให้เข้าใจประสบการณ์การบริหารงานของหัวหน้าหอผู้ป่วยที่ได้รับรางวัลดีเด่น ซึ่งผู้บริหารทางการพยาบาลสามารถใช้เป็นข้อมูลพื้นฐานในการวางแผนพัฒนาหัวหน้าหอผู้ป่วยต่อไป The purpose of this research was to describe experiences of nursing management of head nurses receiving the outstanding award. Hermeneutic phenomenology was applied as research methodology. Data was collected by using in-depth interviews of head nurses who received the outstanding award from the nurse department in a hospital setting. Data analysis followed Diekelman’s content analysis was used in this study. Experiences of nursing management of head nurses receiving the outstanding award consisted of 3 major themes as follows: 1. Improving herself by using self development of good performance consisted of 1.1) Learning good performance from others, 1.2) Seeking knowledge and having life long learning and 1.3) Building work - life balance. 2. Supporting staffs performance consisted of 2.1) Giving opportunity to create innovation, 2.2) Providing professional development, 2.3) Giving good advices when staff needed, 2.4) Creating a warm working climate and 2.5) Delegating job with authority. 3. Faithfully working for organization benefi consisted of 3.1) Producing unit outcomes based on hospital policy, 3.2) Sincerely leading organization and using justice and Buddhist principle for work, 3.3) Having ability of human resource management and 3.4) Having work engagement, even being tried but never give up. The study fidings provided for more understanding on experiences of the nursing management of head nurses receiving the outstanding award. The nurse managers can use them as guideline for set HRM planning for head nurses.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />